Bridging evidence and policy (BEP) seminar series: Crises and response – development and humanitarian in the MENA - Abdelfattah, Lina Alaaeldin; Jovanovic, Nina (CGIAR, 2024)
Vulnerable communities in the Arab world and MENA region face numerous challenges, including conflicts, resource scarcity, and inequality which exacerbate their situation. The COVID-19 pandemic, rising food prices due to conflicts, natural disasters, and ongoing conflicts in Yemen, Sudan, and Palestine further hinder development opportunities in the region. Agile planning and evidence-based policymaking are needed to address these risks, protect vulnerable communities, and build resilience. With this objective in mind, the “Crises And Response: Development & Humanitarian Aid in Middle East & North Africa (MENA)” seminar was held on March 26, 2024, focusing on the developmental work and recent, novel practices in response to and recovery from crises.